Preventive effects of tonsil‐derived mesenchymal stem cells on osteoradionecrosis in a rat model. Issue 3 (15th November 2017) - Park, Hae Sang; Lee, Jihae; Kim, Jin‐Woo; Kim, Ha Young; Jung, Soo Yeon; Lee, Sung Min; Park, Chan Hum; Kim, Han Su
Abstract: Background: The purpose of this study was to investigate the effects of tonsil‐derived mesenchymal stem cells (MSCs) on osteoradionecrosis (ORN). Method: We generated a mandibular ORN rat model using a combination of 20‐Gy single‐dose irradiation and tooth extraction. Study groups were negative control (tooth extraction only), ORN group (irradiation, tooth extraction), Matrigel‐1 group (Matrigel; BD Biosciences, San Jose, CA; irradiation, Matrigel application immediately after tooth extraction), tonsil‐derived MSC‐1 group (irradiation, tonsil‐derived MSC application immediately after tooth extraction), Matrigel‐4 group (irradiation, Matrigel application 4 weeks after tooth extraction), and tonsil‐derived MSC‐4 group (irradiation, tonsil‐derived MSC application 4 weeks after tooth extraction). Result: Bone mineral density was significantly lower in the ORN group than in the negative control group. The tonsil‐derived MSC‐1 group showed significantly higher bone mineral density than did the ORN and tonsil‐derived MSC‐4 groups. Conclusion: A single 20‐Gy dose of irradiation combined with tooth extraction successfully generated ORN in the rat model. The tonsil‐derived MSCs can be effective for bone regeneration in ORN, particularly when applied immediately after dentoalveolar trauma or surgery.